Comparing Ipsilateral and Contralateral Laminotomy with Bilateral Decompression in Cases with Far Lateral Disk Herniation and Lumbar Spinal Stenosis - Akar, Ezgi; Öğrenci, Ahmet; Koban, Orkun; Yılmaz, Mesut; Dalbayrak, Sedat (Indian Journal of Neurosurgery, 2021)
Introduction The aim of this study was to compare clinical results of bilateral decompression and laminotomy and contralateral laminotomy following discectomy from the same side in patients who have far lateral disk herniation and lumbar spinal stenosis at the same level.Materials and Methods Twenty-four patients with far lateral disk herniation have been divided into two groups: group 1 (n = 14), those who have been through bilateral canal decompression with far lateral discectomy and ipsilateral approach, and group 2 (n = 10), those who have been through far lateral discectomy and bilateral decompression with unilateral approach from contralateral side. Early postoperative, 1st month, and 12th month back and leg pain Visual Analogue Scale (VAS) scores of the patients have been retrospectively evaluated.Results There is no significant difference between 1st month back and leg pain VAS scores of the groups. But 12th month back and leg pain VAS scores of group 1 are significantly higher than 1st month VAS scores. Also, 12th month back and leg pain VAS scores of group 1 are significantly higher than group 1. In the scanning carried out when the complaints of eight patients in group 1 continued, pars interarticularis fracture has been observed on the side where the surgery has been performed (57.1%). Six of these eight patients have been through stabilization surgery (42.8%).Conclusion Long-term postoperative results are better in cases who have been performed bilateral decompression with unilateral approach from contralateral side with median incision following paramedian incision discectomy in patients with far lateral disk herniation and spinal stenosis.
Keywords: spinal stenosis; far lateral disk herniation; unilateral approach; contralateral; pars interarticularis